(untitled) (International Journal of Engineering and Computer Science, 2017)
The model described for the use of Provable data Possession which allow the client to access the stored data at an Untrusted server that the server possesses the original data without retrieving it. This model executes the probabilistic proof of possession by random set of blocks which is derived from the server that dramatically reduces the cost of I/O. Sometimes the Client maintenance the constant amount of data which is used to verify the proof. The response protocol can transmit a small amount of data, which can minimize network communication. The two provably –Securer PDP Schemes presents more efficient schemes than previous solution .Even when compared with schemes that achieve weaker guarantees. It is the widely distributed storage systems. Using the experiment we can implement and verify the practicality of PDP and we can revel that the performance of the PDP that is bounded by disk I/O and that cannot be determined by computation.